American Theatre. - Gordon, John C. (photographer):::Creator::::::::::::
American Theatre with Berkova Productions movie equipment and automobile outside of the theatre. The theatre is playing "Hands Across the Border", a western movie, starting Fred Thomson, a silent movie star in the 1920s.